Age-period-cohort analysis of incidence, mortality and disability-adjusted life years of esophageal cancer in global, regional and national regions from 1990 to 2019 - Huiying Li; Xianzhi Yang; Aiqi Zhang; Guanying Liang; Yue Sun; Jian Zhang (BMC, 2024)
Abstract Objective In view of the high incidence and mortality of esophageal cancer, the latest statistical data on the disease burden of esophageal cancer can provide strategies for cancer screening, early detection and treatment, and help to rationally allocate health resources. This study provides an analysis of the global disease burden and risk factors of esophageal cancer from 1990 to 2019. Methods Using the 2019 Global Burden of Disease, Injury and Risk Factor (GBD) data, we present the incidence, mortality and disability-adjusted life years (DALY) of esophageal cancer in 21 regions and 204 countries and different sociodemographic index (SDI) regions from 1990 to 2019. The age-period-cohort model was used to estimate the age, period, and cohort trend of esophageal cancer in different SDI regions. The estimated proportion of DALY attributable to each risk factor from 1990 to 2019. Results From 1990 to 2019, the number of new cases of esophageal cancer, the number of deaths and DALY increased by 67.07%, 55.97% and 42.13%, respectively, but age standardized incidence rate (ASIR), age standardized mortality rate (ASMR) and age standardized DALY rate (ASDR) decreased by 19.28%, 25.32% and 88.22%, respectively. Overall, the results of the age-period-cohort model showed that the incidence, mortality, and DALY rates in countries and regions with higher SDI levels showed a downward trend over time and with the passage of time. Conversely, there were no significant changes in incidence and mortality in countries and regions with low SDI levels. In the past 30 years, the incidence and death of esophageal cancer in the world has gradually changed to people over 80 years old, but the population aged 60-79 still accounts for the largest proportion. The global DALY in esophageal cancer is mainly attributable to smoking, followed by alcohol consumption and occupational exposure. Conclusions Although ASIR, ASMR and ASDR have decreased significantly, esophageal cancer is still the main factor causing the disease burden worldwide. Public health administrators in low SDI and low-middle SDI countries are high-risk areas for esophageal cancer, and preventive control measures should be implemented to raise awareness, screening, and treatment of esophageal cancer in these areas. Tobacco and alcohol control and reduction of occupational hazards are key steps in reducing the burden of esophageal cancer.